Oriented Thin Films of Electroactive Triphenylene Catecholate-Based Two-Dimensional Metal–Organic Frameworks - Mähringer, Andre; Jakowetz, Andreas C; Rotter, Julian M; Bohn, Bernhard J; Stolarczyk, Jacek K; Feldmann, Jochen; Bein, Thomas; Medina, Dana D (ACS nano, 2019)
Two-dimensional triphenylene-based metal–organic frameworks (TP-MOFs) attract significant scientific interest due to their long-range order combined with significant electrical conductivity. The deposition of these structures as oriented films is expected to promote their incorporation into diverse optoelectronic devices. However, to date, a controlled deposition strategy applicable for the different members of this MOF family has not been reported yet. Herein, we present the synthesis of highly oriented thin films of TP-MOFs by vapor-assisted conversion (VAC). We targeted the M-CAT-1 series comprising hexahydroxytriphenylene organic ligands and metal-ions such as Ni2+, Co2+, and Cu2+. These planar organic building blocks are connected in-plane to the metal-ions through a square planar node forming extended sheets which undergo self-organization into defined stacks. Highly oriented thin Ni- and Co-CAT-1 films grown on gold substrates feature a high surface coverage with a uniform film topography and thickness ranging from 180 to 200 nm. The inclusion of acid modulators in the synthesis enabled the growth of films with a preferred orientation on quartz and on conductive substrates such as indium-doped tin oxide (ITO). The van der Pauw measurements performed across the M-CAT-1 films revealed high electrical conductivity values of up to 10–3 S cm–1 for both the Ni- and Co-CAT-1 films. Films grown on quartz allowed for a detailed photophysical characterization by means of UV–vis, photoluminescence, and transient absorption spectroscopy. The latter revealed the existence of excited states on a nanosecond time scale, sufficiently long to demonstrate a photoinduced charge generation and extraction in Ni-CAT-1 films. This was achieved by fabricating a basic photovoltaic device with an ITO/Ni-CAT-1/Al architecture, thus establishing this MOF as a photoactive material. Our results point to the intriguing capabilities of these conductive M-CAT-1 materials and an additional scope of applications as photoabsorbers enabled through VAC thin-film synthesis.